Unemployment dynamics and the cost of business cycles - Jean-Olivier Hairault; François Langot; Sophie Osotimehin (Institute for the Study of Labor (IZA), 2008)
In this paper, we investigate whether business cycles can imply sizable effects on average unemployment. First, using a reduced-form model of the labor market, we show that job finding rate fluctuations generate intrinsically a non-linear effect on unemployment: positive shocks reduce unemployment less than negative shocks increase it. For the observed process of the job finding rate in the US economy, this intrinsic asymmetry is enough to generate substantial welfare implications. This result also holds when we allow the job finding rate to be endogenous, provided the structural model is able to reproduce the volatility of the job finding rate. Moreover, the matching model embeds other non-linearities which alter the average job finding rate and so the business cycle cost.
urn:nbn:de:101:1-20081127694
Keywords: E32; 330; Business cycle costs; unemployment dynamics; Konjunktur; Gesamtwirtschaftlicher Konsum; Soziale Kosten; Arbeitslosigkeit; Hysteresis; Arbeitsuche; Matching; Theorie; USA